PENGEMBANGAN MODUL SUB KOMPETENSI PERAWATAN TANGAN DAN RIAS KUKU UNTUK MENINGKATKAN KREATIVITAS DAN HASIL BELAJAR SISWA DI SMK - Pradani, Rizky Yulianingrum; Nurlaela, Luthfiyah (PENDIDIKAN VOKASI:TEORI DAN PRAKTIK, 2014)
AbstractThe purposes of this study was to determine: 1) the feasibility of modules developed for supporting problem-based learning , 2 ) the activities of teachers and students in teaching and learning activities using hand care and nail make up (manicure) module which is a problem-based learning , 3 ) the differences in creativity between students who use the module in a problem-based learning module and students who do not , 4 ) the differences in learning outcomes between student between students who use the module in a problem-based learning module and students who do not , 5 ) students' response to the application of the learning modules in the hands care and manicures material.The type of this research is the development followed by experimental research. The instruments will be used : 1) validation sheet , 2) activity questionnaire of students and teachers, 3) students questionnaire responses, 4) learning management observation sheet, 5) student?s creativity test, 6) final test. This research is the development research of R&D models developed by Sugiyono, and the goal is the modules development for 10th grader vocational students in the 1st Semester, and target trials were students of skin care in SMKN 1 Batu and SMKN 2 Boyolangu, Tulungagung.Based on the analysis and research it can be concluded that: 1) learning management using module obtain the average 3 observers rating of 3.96 with the percentage in SMK Negeri 1 Batu is 93.33% and in SMK Negeri 2 Boyolangu is 92.5% so it can be categorized as good, 2) the activity that students often do is making creation reached 35.0 % to 50.0% while the activity that is rarely done by students is an activity that is not relevant as much as 0%, 3) in the experimental class completeness of individual experiments reached 81.68 % with a 21.280-t-test and class control reached 72.57% with a 9.469-t-test, 4) creativity student test data , there are 2 students from 60 students who get the highest score that is 16 and the lowest 1 students get 9, and 5) it can be concluded that the modules used in teaching students gives highly positive responses (98%). Keywords: Learning Module, Creativity, learning results, Hand Care and Makeup Nail (Manicure) Sub Competence.